ESG Score, Board Structure and Financial Performance - Nurul Nazlia Jamil; Ersa Tri Wahyuni (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 2 Page (14–26)